Cognitive Interventions and Nutritional Supplements (The CINS Trial): A Randomized Controlled, Multicenter Trial Comparing a Brief Intervention With Additional Cognitive Behavioral Therapy, Seal Oil, and Soy Oil for Sick-Listed Low Back Pain Patients. Issue 20 (15th October 2016) - Reme, Silje E.; Tveito, Torill H.; Harris, Anette; Lie, Stein Atle; Grasdal, Astrid; Indahl, Aage; Brox, Jens Ivar; Tangen, Tone; Hagen, Eli Molde; Gismervik, Sigmund; Ødegård, Arit; Fr⊘yland, Livar; et al.
Abstract : Study Design: A randomized controlled trial. Objective: The aim of this study was to evaluate whether a tailored and manualized cognitive behavior therapy (CBT) or nutritional supplements of seal oil and soy oil had any additional benefits over a brief cognitive intervention (BI) on return to work (RTW). Summary of Background Data: Brief intervention programs are clinically beneficial and cost-effective for patients with low back pain (LBP). CBT is recommended for LBP, but evidence on RTW is lacking. Seal oil has previously been shown to have a possible effect on muscle pain, but no randomized controlled trials have so far been carried out in LBP patients. Methods: Four hundred thirteen adults aged 18 to 60 years were included. Participants were sick-listed 2 to 10 months due to LBP. Main outcome was objectively ascertained work participation at 12-month follow-up. Participants were randomly assigned to BI (n = 100), BI and CBT (n = 103), BI and seal oil (n = 105), or BI and soy oil (n = 105). BI is a two-session cognitive, clinical examination program followed by two booster sessions, while the CBT program is a tailored, individual, seven-session manual-based treatment. Results: At 12-month follow-up, 60% of the participants in the BI group, 50% in the BI and CBT group, 51% in the BI and seal oil group, and 53% in the BI and soy oil group showed reduced sick leave from baseline, and had either partly or fully RTW. The differences between the groups were not statistically significant (χ 2 = 2.54, P = 0.47). There were no significant differences between the treatment groups at any of the other follow-up assessments either, except for a significantly lower sick leave rate in the BI group than the other groups during the first 3 months of follow-up (χ 2 = 9.50, P = 0.02). Conclusion: CBT and seal oil had no additional benefits over a brief cognitive intervention on sick leave. The brief cognitive intervention alone was superior in facilitating a fast RTW. Level of Evidence: 2